2018
DOI: 10.3390/molecules23071502
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimension Diffusion Preparation of Concentration-Gradient Fe2O3/SiO2 Aerogel

Abstract: Concentration-gradient Fe2O3/SiO2 aerogels were prepared by placing an MTMS (methyltrimethoxysilane)-derived SiO2 aerogel on an iron gauze with an HCl atmosphere via one-dimensional diffusion, ammonia-atmosphere fixing, supercritical fluid drying and thermal treatment. The energy dispersive spectra show that the Fe/Si molar ratios change gradually from 2.14% to 18.48% with a height of 40 mm. Pore-size distribution results show that the average pore size of the sample decreases from 15.8 nm to 3.1 nm after diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…For a long time, as a representative of inorganic aerogels, silica aerogels have been widely studied and applied because of their low cost and good structure and properties [7,8]. In the field of biomedicine, previous studies have shown the diffusion mechanism of drugs in silica aerogels [9,10], and that silica nanoparticle-loaded drugs have had good targeted therapeutic effects on diseases [11,12]. In recent years, considering the degradability of materials, scientists have turned their attention to the development of natural polymers [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a long time, as a representative of inorganic aerogels, silica aerogels have been widely studied and applied because of their low cost and good structure and properties [7,8]. In the field of biomedicine, previous studies have shown the diffusion mechanism of drugs in silica aerogels [9,10], and that silica nanoparticle-loaded drugs have had good targeted therapeutic effects on diseases [11,12]. In recent years, considering the degradability of materials, scientists have turned their attention to the development of natural polymers [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, cellulose aerogel was also a promising carrier material for drugs, enzymes, and proteins [21]. It can play a role in controlling release [22] and targeted transportation [10]. In addition, the stability of the drug can also be improved [23].…”
Section: Introductionmentioning
confidence: 99%
“…Hukum Fick (96)(97)(98)(99)(100)(101) Persamaan ini tertata ulang menjadi hasil yang sangat penting, yang dikenal sebagai hubungan Einstein, antara oefisien difusi dengan mobilitas ion (88)(89)(90)(91) .…”
Section: ) Hubungan Einsteinunclassified
“…elektron (56)(57)(58)(59)(60)(61)(62)(63)(64) yang digunakan untuk membentuk ikatan kovalen polar (65)(66)(67)(68)(69)(70)(71)(72)(73) lebih kuat tertarik pada salah satu atom. Parameter transfer ion (74)(75)(76)(77)(78) disini yaitu kecepatan hanyut (79)(80)(81)(82) , bilangan transport (83)(84)(85)(86)(87) , mobilitas ion (88)(89)(90)(91) , difusi (92)(93)(94)(95) , dan hukum I Fick (96)(97)(98)(99)(100)(101) dari senyawa perak sulfat (Ag2SO4).…”
unclassified
“…In order to get higher energy density several strategies have been explored to design and fabricate electrode materials with various porous and hierarchical nanostructures, which are conducive to enhance specific capacitances and modify the rate performances [4][5][6][7][8]. Iron oxides (such as Fe 2 O 3 and Fe 3 O 4 ) have been brought into focus as electrode candidates for supercapacitors in a variety of materials [9][10][11][12]. Specifically, α-Fe 2 O 3 materials have been synthesized and reported elsewhere because of their high theoretical capacitance, low cost, and abundant chemical valences.…”
Section: Introductionmentioning
confidence: 99%